Bone morphogenetic protein 4 inhibits liposaccharide‐induced inflammation in the airway. Issue 11 (25th September 2014) - Li, Zhengtu; Wang, Jian; Wang, Yan; Jiang, Hua; Xu, Xiaoming; Zhang, Chenting; Li, Defu; Xu, Chuyi; Zhang, Kedong; Qi, Yafei; Gong, Xuefang; Tang, Chun; et al.
<x xml:space="preserve">Abstract</x> Bone morphogenetic protein 4 (BMP4) is a multifunctional growth factor that belongs to the TGF‐β superfamily. The role of BMP4 in lung diseases is not fully understood. Here, we demonstrate that BMP4 was upregulated in lungs undergoing lipopolysaccharide (LPS)‐induced inflammation, and in airway epithelial cells treated with LPS or TNF‐α. BMP4 mutant (BMP4+/−) mice presented with more severe lung inflammation in response to LPS or Pseudomonas aeruginosa, and lower bacterial load compared with that in BMP4+/+ mice. Knockdown of BMP4 by siRNA increased LPS and TNF‐α‐induced IL‐8 expression in 16HBE human airway epithelial cells and in primary human bronchial epithelial cells. Similarly, peritoneal macrophages from BMP4+/− mice produced greater levels of TNF‐α and keratinocyte chemoattractant (KC) upon LPS treatment compared with cells from BMP4+/+ mice. Administration of exogenous BMP4 attenuated the upregulation of TNF‐α, IL‐8, or KC induced by LPS and/or TNF‐α in airway epithelial cells, and peritoneal macrophages. Finally, partial deficiency of BMP4 in BMP4+/− mice protected the animals from restrictive lung function reduction upon chronic LPS exposure. These results indicate that BMP4 plays an important anti‐inflammatory role, controlling the strength and facilitating the resolution of acute lung inflammation; yet, BMP4 also contributes to lung function impairment during chronic lung inflammation.